Fast radio bursts. Issue 1 (1st February 2021) - Chatterjee, Shami
Abstract : Shami Chatterjee reviews fast radio bursts, focusing on the rapid recent progress in observations of these enigmatic events, our understanding of their central engines, and their use as probes of the intergalactic medium Abstract: Shami Chatterjee reviews fast radio bursts, focusing on the rapid recent progress in observations of these enigmatic events, our understanding of their central engines, and their use as probes of the intergalactic medium